2022
DOI: 10.1136/bmjqs-2022-014896
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effect of the COVID-19 pandemic on hospital mortality in patients with hip fracture: a competing risk survival analysis using linked administrative data

Abstract: BackgroundHip fracture is a leading cause of disability and mortality among older people. During the COVID-19 pandemic, orthopaedic care pathways in the National Health Service in England were restructured to manage pressures on hospital capacity. We examined the indirect consequences of the pandemic for hospital mortality among older patients with hip fracture, admitted from care homes or the community.MethodsRetrospective analysis of linked care home and hospital inpatient data for patients with hip fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(70 reference statements)
1
3
0
Order By: Relevance
“… 21 Moreover, prior analyses have tended to be disease- or procedure-specific and have not taken a system-level view across diseases and countries. 22 We now confirm previous reports of reduced activity for admissions and for PCI and other CVD-related procedures, showing variation by timing, speed, and extent of recovery across subtypes. Given the significant backlogs across services in the UK 23–25 and other countries, 26 there is an urgent need to monitor and understand these indirect impacts of the COVID-19 pandemic, to develop coordinated, but tailored responses, based on subtype, type and urgency of care, and country.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 21 Moreover, prior analyses have tended to be disease- or procedure-specific and have not taken a system-level view across diseases and countries. 22 We now confirm previous reports of reduced activity for admissions and for PCI and other CVD-related procedures, showing variation by timing, speed, and extent of recovery across subtypes. Given the significant backlogs across services in the UK 23–25 and other countries, 26 there is an urgent need to monitor and understand these indirect impacts of the COVID-19 pandemic, to develop coordinated, but tailored responses, based on subtype, type and urgency of care, and country.…”
Section: Discussionsupporting
confidence: 88%
“…Despite multiple analyses of indirect effects in the UK and other countries using EHR (11)(12)(13)(14)20), these effects have been neglected in pandemic surveillance and policy responses (21). Moreover, prior analyses have tended to be disease-or procedure-specific and have not taken a system-level view across diseases and countries (22). We now confirm previous reports of reduced activity for admissions and for PCI and other CVD-related procedures, showing variation by timing, speed and extent of recovery across subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of BMJ Quality and Safety , Grimm et al 4 allow us to do both. They analysed national administrative data for England (Hospital Episodes Statistics, HES) for the period of March 2019 to February 2021, comparing mortality and length of stay since the pandemic onset with the year before for three patient groups depending on their usual residence: own home (ie, community based), residential home and nursing home.…”
mentioning
confidence: 99%
“…Another facet of redeployment is that one might expect consultant surgeons to perform more hip fracture cases as they are less likely to be performing elective surgery. In this context, it might appear surprising that fewer total hip replacements were performed relative to hemiarthroplasties in the Grimm et al hip fracture cohort4 as, during the pandemic, trained joint replacement surgeons were often redeployed from elective work to trauma care (including the treatment of patients with hip fracture). However, this reflects a broader trend observed since the publication of the hip fracture evaluation with alternatives of total hip arthroplasty versus hemiarthroplasty (HEALTH) randomised trial, which suggested that total hip replacement for patients with hip fracture was not as superior to alternative treatment options as reported by previous studies 11.…”
mentioning
confidence: 99%